Genomic insights on carotenoid synthesis by extremely halophilic archaea Haloarcula rubripromontorii BS2, Haloferax lucentense BBK2 and Halogeometricum borinquense E3 isolated from the solar salterns of India - Devika. N. Nagar; Kabilan Mani; Judith M. Braganca (Scientific Reports, 2024)
Abstract Haloarchaeal cultures were isolated from solar salterns of Goa and Tamil Nadu and designated as BS2, BBK2 and E3. These isolates grew with a characteristic bright orange to pink pigmentation and were capable of growing in media containing upto 25% (w/vol) NaCl. Whole genome sequencing (WGS) of the three haloarchaeal strains BS2, BBK2 and E3 indicated an assembled genomic size of 4.1 Mb, 3.8 Mb and 4 Mb with G + C content of 61.8, 65.6 and 59.8% respectively. Phylogenetic analysis based on the 16S rRNA gene sequence revealed that the archaeal isolates belong to Haloarcula, Haloferax and Halogeometricum genera. Haloarcula rubripromontorii BS2  was predicted to have 4292 genes with 4242 CDS regions, 46 tRNAs, 6 rRNAs and 3 misc_RNAs. In case of Haloferax lucentense  BBK2, 3840 genes with 3780 CDS regions were detected along with 52 tRNAs, 5 rRNAs and 3 misc_RNAs. Halogeometricum borinquense  E3 contained 4101 genes, 4043 CDS regions, 52 tRNAs, 4 rRNAs, and 2 misc_RNAs. The functional annotation and curation of the haloarchaeal genome, revealed C50 carotenoid biosynthetic genes like phytoene desaturase/carotenoid 3′ -4′ desaturase (crtI), lycopene elongase (ubiA/lyeJ) and carotenoid biosynthesis membrane protein (cruF) in the three isolates. Whereas crtD (C-3′,4′ desaturase), crtY (lycopene cyclase) and brp/blh (β-carotene dioxygenase) genes were identified only in BS2.